2017
DOI: 10.1093/nutrit/nuw058
|View full text |Cite
|
Sign up to set email alerts
|

Dietary assessment in minority ethnic groups: a systematic review of instruments for portion-size estimation in the United Kingdom

Abstract: Context: Dietary assessment in minority ethnic groups is critical for surveillance programs and for implementing effective interventions. A major challenge is the accurate estimation of portion sizes for traditional foods and dishes. Objective: The aim of this systematic review was to assess records published up to 2014 describing a portion-size estimation element (PSEE) applicable to the dietary assessment of UK-residing ethnic minorities. Data sources, selection, and extraction: Electronic databases, interne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 71 publications
1
31
0
Order By: Relevance
“…The use of dietary records or recalls allows for a range of different eating patterns to be recorded, unlike the fixed food lists of an FFQ. Consideration also needs to be made around customary portion sizes by age and sex when developing ethnic-specific DATs [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…The use of dietary records or recalls allows for a range of different eating patterns to be recorded, unlike the fixed food lists of an FFQ. Consideration also needs to be made around customary portion sizes by age and sex when developing ethnic-specific DATs [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…Two studies have reported sex-specific portion sizes for assessing dietary intake. 11, 28 For instance, Cade et al 11 reported that it may be appropriate to use sex-specific ‘typical’ portions instead of ‘standard’ portions to estimate nutrient intake from a FFQ because the variation in most foods in portion size within individuals exceeded that between individuals. Recently, Almiron-Roig et al 28 noted that reference portion sizes in a FFQ need to be representative of the ethnic group studied and to account for sex and age differences, especially for amorphous foods such as rice and noodle dishes.…”
Section: Discussionmentioning
confidence: 99%
“…11, 28 For instance, Cade et al 11 reported that it may be appropriate to use sex-specific ‘typical’ portions instead of ‘standard’ portions to estimate nutrient intake from a FFQ because the variation in most foods in portion size within individuals exceeded that between individuals. Recently, Almiron-Roig et al 28 noted that reference portion sizes in a FFQ need to be representative of the ethnic group studied and to account for sex and age differences, especially for amorphous foods such as rice and noodle dishes. In the present study, using data from a multiethnic population, intakes of “white rice” and “brown or wild rice” differed between men and women even when they selected the same usual portion size; there was also a sex difference in comparison with the standard amount of the selected portion size, even though the QFFQ2 portion sizes were given in specific units, such as 1 cup, rather than as generic labels, such as “small”.…”
Section: Discussionmentioning
confidence: 99%
“…We examined the following concepts:Do dietary patterns differ between PD patients of Black African and Caribbean and Asian groups of either first or second generation resident in the United Kingdom compared to White PD patients [10]?Is dietary supplement use different between the White and the non-White PD groups? Specifically, we would look at intake of vitamin D, turmeric, coffee, and black tea as these have been associated with possible effects on the natural history of PD [2].…”
Section: Introductionmentioning
confidence: 99%
“…Do dietary patterns differ between PD patients of Black African and Caribbean and Asian groups of either first or second generation resident in the United Kingdom compared to White PD patients [10]?…”
Section: Introductionmentioning
confidence: 99%